2005
DOI: 10.1007/s11240-004-6660-3
|View full text |Cite
|
Sign up to set email alerts
|

Shoot regeneration from nodules of Charybdis sp.: a comparison of semisolid, liquid and temporary immersion culture systems

Abstract: Nodules of Charybdis numidica maintained in liquid Murashige and Skoog (MS) medium with 20 lmol BA in the dark were subjected to different treatments under continuous light for shoot regeneration. A high regeneration rate without hyperhydration of the shoots was observed on semisolid basal MS medium with 1% sucrose. The use of liquid MS medium (1% sucrose, no growth regulators) resulted in a significantly lower amount of shoots per gramme of nodules under both submerged and temporary immersion (TI) conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Similar results were reported from temporary immersion bioreactor system reported by Wawrosch et al (2005), Zhu et al (2005) and Adelberg (2005). According to Etienne and Berthouly (2002), bioreactor systems combine the advantages of solid cultures (maximum gas exchanges) and liquid media (increased nutrient uptake).…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were reported from temporary immersion bioreactor system reported by Wawrosch et al (2005), Zhu et al (2005) and Adelberg (2005). According to Etienne and Berthouly (2002), bioreactor systems combine the advantages of solid cultures (maximum gas exchanges) and liquid media (increased nutrient uptake).…”
Section: Discussionsupporting
confidence: 83%
“…Previous results indicated that plantlets developed via ex vitro rooting methods had an extensive root system with many secondary roots and without callus growth at the base of plantlets, just like the natural root system of S. grosvenorii (Yan et al 2010). The temporary immersion system (TIS), which is based on the principle that temporary contact between plants and liquid medium is preferable to permanent contact, has been extensively used for micropropagation (Alvard et al 1993;Cabasson et al 1997;Lorenzo et al 1998;Martre et al 2001;Wawrosch et al 2005;Thomas et al 2008;Alonso et al 2009). Compared with gelled and liquid culture, the TIS has been proven to have quantitative advantages such as higher proliferation rate, higher somatic embryogenesis, improved morphological characteristics and reduced production cost (Etienne and Berthouly 2002).…”
Section: Abbreviationsmentioning
confidence: 99%
“…This unusual growth pattern may be attributed to prolonged growth in liquid medium under slow agitation. It has been reported that continuous agitation obstructs apical dominance which ultimately leads to increased adventitious branching (Wawrosch et al 2005, Kongbangkerd andWawrosch 2003). In addition to the steady production of root biomass (Table 1), production of shoots was also noticed in long term cultures (12 weeks or more, Fig.…”
Section: Resultsmentioning
confidence: 71%